PENERAPAN METODE PROTOTYPE DALAM PERANCANGAN BIMBINGAN MASYARAKAT PADA KEMENTRIAN AGAMA SATUAN KERJA OGAN ILIR - Ardiansyah, Arif; Fadilah , Evi (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
The Islamic Community Guidance at the Ministry of Religion is tasked with providing services, technical guidance, data and information management, as well as planning and reporting in the field of Islamic religious affairs and sharia development, building religious affairs offices and sakinah families, as well as Islamic religious information. dissatisfied with BIMAS services because registering for services alone can take a long time because it is still done manually, BIMAS data archiving is still archived in the ledger and BIMAS information giving must call or send messages to participants one by one. These constraints are deemed less effective in the implementation of BIMAS services. The method used is the Prototype method by using system development tools such as DFD and ERD. In designing the BIMAS information system, it aims to facilitate the community in providing services such as technical guidance services, marriage guidance and MTQ competitions.